To Identify the Untrustworthy Leader of a Hierarchical Wireless Sensor Network Using Received Signal Strength - Abdullah, Md. Ibrahim; Rahman, Md. Atiqur; Hossain, Mohammad Alamgir; Islam, Md. Shohidul; Hossain, Md. Shamim (International Journal of Scientific Research in Computer Science and Engineering, 2022)
There are a multitude of privacy and safety concerns that arise as a result of wireless sensor nodes being carelessly put in potentially hazardous regions. An adversary has the capability of either seizing a node that is located in an area that is not under their control or introducing a node that is acting under the guise of a genuine node. The lack of adequate security in sensor networks presents a substantial barrier to many potential applications. A form of protection known as intrusion detection can be utilized to thwart attacks of this nature. Because of this, traditional methods of intrusion detection cannot be utilized in a sensor network due to the restricted resources of individual nodes. In this paper, we have presented a method to detect intruder in hierarchical wireless sensor networks using a sensor fusion algorithm. This method is intended to be utilized in situations in which malevolent nodes are performing the duties of Cluster Head. Clustering is an approach that sensor networks take in order to produce their detections. A technique that only requires a modest amount of communication yet is nevertheless capable of thwarting an attack on a hierarchical routing system has been described.